Traditional Usages of Taro (Colocasia spp.) by Ethnic Communities in Borneo - Oktavianingsih, Linda; Suharyanto, E.; Daryono, Budi Setiadi; Purnomo, Purnomo (Biosaintifika: Journal of Biology & Biology Education, 2017)
Borneo has a a wealth of various flora, including the Aroids (Araceae). Taro is one of the Aroids that cultivated and used as food crop since a long time ago by the people in Borneo. This study aimed to determine the utilization of Taros traditionally by several ethnic communities in Borneo. The research used Survey Explorative Method with Direct Interview Technique in the field. Taro samples were taken from various habitats of Banjar, Dayak, Kutai, Malay, Bugis, Toraja and China ethnic. The results showed that Taro species widely used are : Colocasia esculenta var. esculenta and var. antiquorum, Colocasia affinis and wild of Colocasiaesculenta. C. esculenta var. esculenta and var. antiquorum is used as subsistence food crop and vegetables. Besides, it is used as medicine such as high blood pressure lowering and for consumption of diabetics. Parts of the plants consumed include leaves, petiole, corm and stolon. C. affinis is used as ornamental plants of the home garden, while wild C. esculenta is used as animal fodder. Taro in Borneo have a considerable variation of traditional cultivars and vernacular names. Fifty eight traditional cultivars from 5 different habitat to be used by some ethnics.